Sayings from the farming sector: myths or reality according to knowledge of farmers in southern Ecuador. - Paccha Tamay, Karina; Capa-Mora, Edwin Daniel; Carrera Durazno, Rubén; Fierro Jaramillo, Natacha; Jiménez Álvarez, Leticia (Agricultura, Sociedad y Desarrollo, 2025)
Farmers have a wide range of sayings and phrases that are transmitted from generation to generation and which reflect their knowledge and view on farm life and work. The objective of this study was to identify the most relevant sayings in the rural sector, according to the perception of farmers from the rural area of the Province of Loja (Ecuador), and to determine if these sayings are myths or of they represent realities in the rural environment. For this purpose, information was gathered from farmers, through 251 semi-structured surveys, where informative contents were addressed, such as: gender, age, education level, sayings from the agriculture and livestock sector; the group was chosen taking into account the availability of the people and it was centered in those who were involved in the farming activity. The results were entered into Excel and analyzed with a Chi-squared test (p<0.05), to identify statistically significant differences; these showed that the survey respondents, regardless of their age, gender or education level, know about agricultural and livestock sayings and that these are constantly used to develop agriculture and livestock production activities such as sowing, pruning and other farming tasks. However, the study finds that not all the sayings have a scientific support, although many of them agree with agroproductive technical knowledge. The sayings are considered as a valuable form of ancestral knowledge and deserve to be reassessed and preserved for the future generations.